SVA: The Power of Assertions in System Verilog - Cerny, Eduard (Springer, 2015)
This book is the result of the deep involvement of the authors in the development of EDA tools, SystemVerilog Assertion standardization, and many years of practical experience. One of the goals of this book is to expose the oral knowhow circulated among design and verification engineers which has never been written down in its full extent. The book thus contains many practical examples and exercises illustrating the various concepts and semantics of the SystemVerilog assertion language. Much attention is given to discussing efficiency of assertion forms in simulation and formal verification. We did our best to validate all the examples, but there are hundreds of them and not all features could be validated since they have not yet been implemented in EDA tools. Therefore, we will be grateful to readers for pointing to us any needed corrections. The book is written in a way that we believe serves well both the users of SystemVerilog assertions in simulation and also those who practice formal verification (model checking). Compared to previous books covering SystemVerilog assertions we include in detail the most recent features that appeared in the IEEE 1800–2009 SystemVerilog Standard and were further improved and enhanced in the recent IEEE 1800–2012 Standard. In particular, it concerns the new encapsulation construct “checker” and checker libraries, Linear Temporal Logic operators, and semantics and usage in formal verification. However, for integral understanding we present the assertion language and its applications in full detail...